Comparison of Different Lymph Node Staging Schemes for Predicting Survival Outcomes in Node-Positive Endometrioid Endometrial Cancer Patients - Yang, Xi-Lin; Huang, Nan; Wang, Ming-Ming; Lai, Hua; Wu, Da-Jun (Frontiers in Medicine, 2021)
Background:To compare the prognostic predictive performance of six lymph node (LN) staging schemes: AJCC N stage, number of retrieved LNs (NRLN), number of positive LNs (NPLN), number of negative LNs (NNLN), LN ratio (LNR) and log odds of positive LNs (LODDS) among node-positive endometrioid endometrial cancer (EEC) patients. Methods:3533 patients diagnosed with node-positive EEC between 2010-2016 from the SEER database were retrospectively analyzed. We applied X-tile software to identify the optimal cut-off value for different staging schemes. Univariate and multivariate cox regression model were used to assess the relationships between different LN schemes and survival outcomes (disease-specific survival: DSS and overall survival: OS). Moreover, Akaike information criterion (AIC) and Harrell concordance index (C-index) were used to evaluate the predictive performance of each scheme in both continuous and categorical patterns. Result: N stage (N1/N2) was not an independent prognostic factor for node-positive EEC patients based on multivariate cox analysis (DSS:P=0.235; OS:P=0.145). Multivariate model incorporating LNR demonstrated the most superior goodness of fit regardless of continuous or categorical pattern. Regarding discrimination power of the models, LNR outperformed other models in categorical pattern (OS: C-index=0.735; DSS: C-index=0.737), however, LODDS obtained the highest C-index in continuous pattern (OS: 0.736; DSS: 0.739). Conclusions:N1/N2 was unable to differentiate the prognosis of node-positive ECC patients. LNR and LODDS schemes seemed to have better predictive performance than other LN schemes, both of which might aid in the revision of staging system for node-positive EEC patients.